KETEBALAN KOMPLEKS INTIMAMEDIA KAROTIS MENGGUNAKAN ULTRASONOGRAFI PADA PASIEN HIV DENGAN INFEKSI OPORTUNISTIK INTRAKRANIAL - Mohammad Arief Rachman*, Salim Harris*, Riwanti Estiasari*, Joedo Prihartono** (NEURONA, 2015)
INTRODUCTION HUMAN IMMUNODEFICIENCY VIRUS HIVINFECTION IS A CHRONIC INFLAMMATORY PROCESS THAT CAUSES ENDOTHELIAL INJURY LEADING TO THICKENING OF THE INTIMA MEDIA COMPLEX CONSEQUENTLY HIV PATIENTS WITH INTRACRANIAL OPPORTUNISTIC INFECTIONS HAVE HIGHER RISKS TO MANIFEST VASCULAR DISTURBANCE ESPECIALLY WITHIN THE CAROTID VESSELS THEREFORE EARLY DETECTION USING CAROTID VESSEL EXAMINATION IS FUNDAMENTAL TO DETERMINE THE NEED FOR PREVENTIVE ACTION AGAINST CEREBROVASCULAR INCIDENTS